MSI2 is required for maintaining activated myelodysplastic syndrome stem cells - James Taggart (Nature Portfolio, 2016)
Several studies have recently demonstrated the role of the MSI2 RNA binding protein in normal and malignant haematopoietc stem cells. In this study, the authors show that MSI2 is required for maintaining myelodysplastic syndrome stem cells in mice and that MSI2 expression predicts poor prognosis in patients affected by this disease.